Interview with the Stutterers: How Do They Manage the Conversation? (an Analysis on Turn-taking Strategies) - Nurfaiza, Salma; Ruminda, Ruminda; Awaludin, Lili (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
Stutterers are people with disfluencies in talking. They have problems maintaining their turn in a conversation. For that reason, they need to find some strategies to manage the conversation well. This study aims to find out what types of turn-taking strategies were used by stuttering people and why they tend to use them. The theories used in this research are from Stenstrom and Bloodstein. The data for this research are taken from three interview YouTube videos with stuttering people. The video was then analyzed based on Stenstrom's turn-taking strategy theory as well as Bloodstein's stuttering theory. The results of the analysis showed that the strategy most often used by the stuttering people is filled pause/verbal filler which is part of the holding the turn strategy. The purpose of this most commonly used strategy is to maintain the stutterer’s turns to speak so that there is no interruption by the interlocutor and it becomes part of the disfluencies suffered by people with stuttering, as a thought process in expressing words.